Profiling Plasma MicroRNA in Nasopharyngeal Carcinoma with Deep Sequencing. (1st May 2014) - Wang, Hai-Yun; Yan, Li-Xu; Shao, Qiong; Fu, Sha; Zhang, Zi-Chen; Ye, Weimin; Zeng, Yi-Xin; Shao, Jian-Yong
Abstract: BACKGROUND: The goal of this study was to establish a plasma microRNA profile by use of next-generation sequencing that could aid in assessment of patient prognosis in nasopharyngeal carcinoma (NPC). METHODS: Two panels of NPC patients and healthy controls (HCs) were recruited for this study. We used deep sequencing to screen plasma microRNAs. Differentially expressed microRNAs were verified by quantitative real-time PCR (qPCR). Kaplan–Meier survival analysis with the log-rank test was used to compare overall survival (OS) and progression-free survival (PFS) between groups. RESULTS: Twenty-three plasma miRNAs with differential expression levels were selected for qPCR analysis on an independent set including 100 NPC patients and 55 HCs. NPC patients with low concentrations of miR-483–5p and miR-103 had better prognosis for 5-year OS than those with high concentrations (87.5% vs 55.8%, P < 0.001; 80.9% vs 62.3%, P = 0.031). Those with low concentrations of miR-29a and let-7c had poorer prognosis (54.8% vs 82.8%, P = 0.002; 56.3% vs 84.6%, P = 0.001). A 3-signature miRNA integrated with clinical stage was further identified in an independent set. We calculated a prognostic index score and classified patients into low-, medium-, and high-risk groups. Five-year OS among the 3 groups was significantly different (90.9%, 66.7%, and 23.8%; P < 0.001). By multivariate analysis, a high-risk score was the most significantly unfavorable prognostic factor independent of other clinical variables ( P < 0.001, hazard ratio = 15.1, 95% CI = 5.2–43.9). CONCLUSIONS: Differentially expressed plasma miRNAs as identified by next-generation sequencing can be helpful for predicting survival in NPC patients.